Contribution of intrinsic and extrinsic motivation factors on job satisfaction of foreign nurses in public hospitals of Hail City, Saudi Arabia - Fahad B, Alsabhan Turki (2021)
High job satisfaction is vital to enhance nursing care, improve daily practice, increase productivity, and enable the delivery of high-quality healthcare, and to maintain a stable nursing work force. Saudi Arabia is very dependent on foreign nurses who comprise of 62% of the nurses who work in the public hospitals. However, the number of these nurses are decreasing from 41,431 in 2016 to 40,208 in 2017, which may be due to job satisfaction factor. The objective of this study is to determine the contribution of intrinsic and extrinsic motivation on job satisfaction of foreign nurses in public hospitals in Hail city, Saudi Arabia. This was a cross-sectional study, conducted among foreign nurses who work in two public hospitals in Hail City, Saudi Arabia. Simple random sampling of 196 foreign nurses were done to select the respondents. Self-administrated questionnaires were distributed manually. The questionnaires consist of four section: section A captured the sociodemographic data, section B measured job satisfaction with extrinsic motivation factors, section C was measured job satisfaction with intrinsic motivation factors, while section D measured the overall job satisfaction level. Analysis was done using SPSS Version 25, which included descriptive analysis to determine the level of job satisfaction, Pearson’s correlation to find the association between intrinsic and extrinsic factors with job satisfaction, and multiple regression for the predicting factors. The SPSS Macros, called PROCESS was used to test if the demographic characteristics moderate the relationship between motivation (intrinsic and extrinsic) and job satisfaction. The level of significance for this study was set up at alpha of 0.05. The majority of foreign nurses (54.1%) in the public hospitals in Hail city, Saudi Arabia had a moderate job satisfaction level. There is a significant and positive relationship between three components of intrinsic motivation including autonomy (r=0.518, p<0.010), mastery (r=0.468, p<0.001) and purpose (r=0.350, p<0.001). Also, while there is significant and positive association between three components of extrinsic motivation of pay (r=0.446, p<0.001), promotion (r=0.445, p<0.001) and operating conditions (r=0.169, p=0.018) with job satisfaction. Of these, autonomy, purpose, mastery, promotion, fringe benefits and operating conditions have statistically significant relationship with the job satisfaction level. Age was able to moderate the relationship between mastery, purpose, pay, promotion, fringe benefits with job satisfaction positively. Similarly, education was able to moderate positively the relationship between purpose and promotion with job satisfaction, salary was able to moderate the relationship between pay with job satisfaction, work experience was able to moderate positively the relationship between pay and promotion with job satisfaction. This study revealed that in public hospitals in Hail City, Saudi Arabia, level of job satisfaction was moderate among most of the foreign nurses. Autonomy, purpose, mastery, promotion, fringe benefits and operating conditions significantly predict the job satisfaction level. It is imperative that nursing managers, hospitals directors, and policy makers in Saudi Arabia apply these factors when considering programs to improve foreign nurses' job satisfaction.